1980
DOI: 10.3354/meps002035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonal Variations of Temperature and Light on the Growth Rate of Cultures and Natural Populations of Intertidal Diatoms

Abstract: Cultures of four benthic diatom species (Navicula salinarum, Amphiprora cf, paludosa, N. arenaria, Gyrosigma spenceni) were kept at the surface of a mudflat in order to measure division rates. During incubations in the period of December to June the mean temperature was the predominant factor regulating cell division rate. Immersion of the mudflat with very turbid tidal water was an important factor only at a low-level mudflat station during winter and early spring. Strong temperature fluctuations during incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 8 publications
4
41
1
Order By: Relevance
“…Admiraal & Peletier, 1980;Rasmussen et al, 1983;van Duyl & Kop, 1990), while relatively few have examined the simultaneous community response towards a number of dominating parameters (e.g. Hargrave et al, 1983;Grant, 1986;Kristensen, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Admiraal & Peletier, 1980;Rasmussen et al, 1983;van Duyl & Kop, 1990), while relatively few have examined the simultaneous community response towards a number of dominating parameters (e.g. Hargrave et al, 1983;Grant, 1986;Kristensen, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are known to have adapted to a wide range of temperatures (e.g., Thomas 1966, Colijn & van Buurt 1975, Admiraal & Peletier 1980, Suzuki & Takahashi 1995, Mock & Hoch 2004, Boyd et al 2013, Thorel et al 2014, Woelfel et al 2014. The non-photosythetic diatoms investigated in the present study are capable of surviving at temperatures from 5 to 35°C, which is wider than that reported for a strain of a closely related species, such as Pseudo-nitzschia australis Frengulli, which has been reported to be capable of growing from 5 to 20°C (Thorel et al 2014).…”
Section: Temperature Tolerancementioning
confidence: 57%
“…This evaporation phenomenon also triggers other severe conditions such as high temperature and high salinity. Nevertheless, it has been reported that various algal species are capable of inhabiting such severe environments (Williams 1964, Mizuno 1992, Colijn & van Buurt 1975, Admiraal & Peletier 1980, Pinckney & Zingmark 1991, Kamikawa et al 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inverse relationships between microphytobenthic biomass and temperature and SR (Figure 3), clearly point to optimal conditions for the establishment of dense populations of cyanobacteria and diatoms, as being in the lower ranges of these two parameters. Accordingly it has been pointed [33] that the temporal distribution of microphytobenthos can be explained partly by the seasonal variation in irradiance and sediment temperature. Studying the influence of different grain sizes and temperatures on the growth of benthic cyanobacteria and diatoms it was found [34] that diatoms achieved the highest biomass on the finest sediments (<63 µm), in a temperature range of 10˚C -15˚C, while cyanobacteria achieved low biomass levels in the same temperature range.…”
Section: Discussionmentioning
confidence: 99%